MSC exosomes attenuate sterile inflammation and necroptosis associated with TAK1-pJNK-NFKB mediated cardiomyopathy in diabetic ApoE KO mice - Banerjee, Abha; Singla, Dinender K. (Frontiers in Immunology, 2024)
Diabetes is a debilitating disease that leads to complications like cardiac dysfunction and heart failure. In this study, we investigated the pathophysiology of diabetes-induced cardiac dysfunction in mice with dyslipidemia. We hypothesize diabetes in ApoE knockout (ApoE-/-) mice induces cardiac dysfunction by increasing inflammation and necroptosis. ApoE-/-mice were divided into experimental groups: Control, Streptozotocin (STZ), STZ + MSC-Exo (mesenchymal stem cell-derived exosomes), and STZ+MEF-Exo (Mouse embryonic fibroblast derived exosomes). At Day 42, we assessed cardiac function, collected blood and heart tissues. STZ treated ApoE-/-mice developed diabetes, with significantly (p<0.05) increased blood glucose and body weight loss. These mice developed cardiac dysfunction with significantly (p<0.05) increased left ventricular internal diameter end diastole and end systole, and decreased ejection fraction, and fractional shortening. We found significant (p<0.05) increased expression of inflammatory cytokines TNF-α, IL-6, IL-1α, IL-33 and decreased IL-10 expression. Diabetic mice also exhibited significantly (p<0.05) increased necroptosis marker expression and infiltration of inflammatory monocytes and macrophages. MSC-Exos treated mice showed recovery of diabetes associated pathologies with significantly reduced blood glucose, recovered body weight, increased IL-10 secretion and M2 polarized macrophages in the heart. These mice showed reduced TAK1-pJNK-NFKB inflammation associated expression and improved cardiac function with significantly reduced cardiac hypertrophy and fibrosis compared to diabetic mice. Treatment with MEF-Exos did not play a significant role in attenuating diabetes-induced cardiomyopathy as these treatment mice presented with cardiac dysfunction and underlying pathologies observed in STZ mice. Thus, we conclude that cardiac dysfunction develops in diabetic ApoE-/-mice, arising from inflammation, necroptosis, and adverse tissue remodeling, which is ameliorated by MSC-Exos, a potential therapeutic for diabetes-induced cardiomyopathy.